Em trânsito: um estudo sobre narrativas de viagem - Modernell, Renato (2009)
The present paper investigates how Travel Narrative is connected to literary fiction. Taking into consideration composition processes, tools of style and thematical hybridism, this study discusses if these narratives can be considered as a significant genre of post-modern culture. Three books appear at first: The last opium den, by Nick Tosches; Woman of Porto Pim, by Antonio Tabucchi; and A fortune-teller told me, by Tiziano Terzani. In these books the authors narrate their impressions while travelling through the southeast of Asia and also through the archipelago of Azores. The Bakhtinian notion of dialogism sustains the theoretical basis of this paper, which compares the two texts between themselves and the others.